Clinical Characteristics of Anti-GABA-B Receptor Encephalitis - Zhu, Fei; Shan, Wei; Lv, Ruijuan; Li, Zhimei; Wang, Qun (Frontiers in Neurology, 2020)
Objective: Anti-GABA-B (gamma aminobutyric acid-B) receptor encephalitis is an autoimmune disease mediated by GABA-B-related antibodies. To fully understand the disease, we collected clinical data from patients with GABA-B receptor encephalitis and conducted an analysis to draw conclusions. Methods: All patients with GABA-B receptor encephalitis from the Neurology Department of Beijing Tiantan Hospital from August 2015 to September 2019 were accepted as study subjects. The clinical data of the patients were analyzed retrospectively and included the general demographic characteristics, clinical manifestations, and auxiliary examinations, including laboratory results, electroencephalograms (EEGs), brain magnetic resonance imaging (MRI), positron emission tomography (PET-CT) results, and treatments. Results: 14 cases of anti-GABA-B receptor encephalitis were diagnosed. Middle-aged men were the main demographic, with an average age of 52 years old; the onset of the disease was relatively sudden, and the time from onset to diagnosis was approximately one month. The main clinical symptoms were frequent epileptic seizures, cognitive dysfunction and mental behavioral disorders. In six (43%) patients, the leukocyte and protein levels in cerebrospinal fluid (CSF) were increased. The CSF oligoclonal bands of 83% patients were positive, and 24 h IgG levels of 92% patients were increased. Anti-Hu or anti-Yo antibodies were positive in two (14%) patients. Tumor markers in ten (71%) patients were increased. EEG results often indicated slow waves, sharp waves or spike waves in temporal areas. Brain MRI showed high T2 signals in the medial temporal lobe, hippocampus. PET-CT scans showed abnormal metabolism in the hippocampus and temporal lobe. Three (21%) patients who underwent systemic PET-CT showed hypermetabolism in pulmonary parenchymal nodules and enlargement of mediastinal lymph nodes. All patients underwent high-dose hormone therapy or immunoglobulin immunotherapy. After treatment, the symptoms of epilepsy, cognitive disorders and mental behavioral disorders improved. However, one patient died of lung cancer. Conclusion: Anti-GABA-B receptor encephalitis mainly occurred in middle-aged men. Before disease onset, some patients experienced fever, which mainly manifested as epileptic seizures, cognitive dysfunction and abnormal mental behavior. MRI and PET-CT revealed abnormal signals and local metabolism, respectively, in the temporal lobe. Moreover, the disease has a close relationship with lung cancer, which requires long-term follow-up observation.